2000
DOI: 10.1093/intqhc/12.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of satisfaction with surgical treatment

Abstract: The central treatment-related measures were the same in the retrospective and prospective studies: global satisfaction with treatment (GS), perceived quality of contact with the nursing (QCN) and medical staff (QCM) and provision of adequate treatment information (INF). More of the variance in GS was explained in the prospective study (48.7% versus 36.3%). GS was most influenced by treatment-related factors with QCN as the strongest predictor in both studies. Only a small portion of the variance in QCN and QCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 0 publications
1
31
1
4
Order By: Relevance
“…Conceptually, HLC is a personality style variable, which has commonly been used as a predictor of medical outcomes, and of the individuals' adaptation to a variety of threatening health issues 23 . We use only the Internal sub-scale, hereunder 5 of the 6 items.…”
Section: Internal Health Locus Of Control (Ihlc)mentioning
confidence: 99%
“…Conceptually, HLC is a personality style variable, which has commonly been used as a predictor of medical outcomes, and of the individuals' adaptation to a variety of threatening health issues 23 . We use only the Internal sub-scale, hereunder 5 of the 6 items.…”
Section: Internal Health Locus Of Control (Ihlc)mentioning
confidence: 99%
“…A problem using patient satisfaction as a quality indicator depends on the complexities where different factors could affect the outcome, and the reliability and validity questioned [17]. Factors such as gratitude, faith and loyalty to health care providers, could influence patient satisfaction [18] as well as background factors such as age, health status and expectations of care [19][20]. A patient's evaluation could be positive, even when care is poor [18].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In particular, patients' satisfaction or dissatisfaction after spinal surgery has been shown to be influenced by patients' expectations, their medical condition and health status, psychosocial variables, and characteristics of the treatment. [8][9][10] These studies included younger age groups and cannot be generalized to the elderly. A recent follow-up study 11 comprising 83 patients reported that patients satisfaction correlated with postoperative back pain, leg pain, numbness and subjective difficulty in walking; however, by multivariate regression analysis the only independent correlate was a subjective walking difficulty, and it was concluded that postoperative level of functioning was weakly correlated with satisfaction.…”
Section: Introductionmentioning
confidence: 99%